2020
DOI: 10.15294/elt.v9i1.38259
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing English for Academic Purposes textbooks in China: A study of intercultural issues

Abstract: An increase of English for Academic Purposes (EAP) teaching in China has resulted in a surge of EAP textbooks on the market. However, there has been little accompanying interest in how well intercultural issues are handled and presented in these publications. Accordingly, the present study employs Chinese students’ Cultures of Learning (CoL) and contrastive rhetoric (CR) as reflection points in the analysis of the content, production, and consumption of two series of EAP textbooks adapted from overseas textboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Though students scored very high in their subject, they demonstrated a complete inability to apply their knowledge in the workplace because they lacked adequate language to deliver their message (Hans & Hans, 2015). Li et al (2020) also found that the books did not include information concerning how a student should learn in their academic study.…”
Section: Professional Communication Gaps In the Target Situationmentioning
confidence: 99%
“…Though students scored very high in their subject, they demonstrated a complete inability to apply their knowledge in the workplace because they lacked adequate language to deliver their message (Hans & Hans, 2015). Li et al (2020) also found that the books did not include information concerning how a student should learn in their academic study.…”
Section: Professional Communication Gaps In the Target Situationmentioning
confidence: 99%